The Threonine Requirements and its Effects on Growth Performance and Gut Morphology of Broiler Chicken Fed Different Levels of Protein - Zaefarian, F.; Zaghari, M.; Shivazad, M. (International Journal of Poultry Science, 2008)
An experiment was conducted to determine the effects of dietary threonine (Thr) and crude protein (CP) on growth performance, gut measurements and morphology and to estimate Standardized Ileal Digestible (SID) Thr requirements of Ross 308 males at 0-21 days of age. The SID Thr levels were 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 and 1.1% with two levels of protein 16 and 19%. Chicks were randomized into 64 battery pens (5 chicks per replicate). FI was lower for broiler given the high CP diets compare to those fed on the low CP diets. BWG and FCR improved up to 0.7% Thr in both CP levels. Weight gain improved non-linearly suggesting optimum dietary SID Thr levels between 0.89 and 0.84% (quadratic) at 16 and 19% ideal protein, respectively. Significant interaction was found between CP and Thr on relative weight and length of duodenum and jejunum (p<0.05). Thr supplementation had significant effect on villus height, epithelial thickness, goblet cell number and crypt depth in duodenum, jejunum and ileum (p<0.01). Low CP diets adequate in Lys, TSAA supplemented with Thr may result in optimal BWG and FCR as well as growth of intestinal length non-linearly. Parameters of gut functionality such as microvilli height, crypt depth and epithelia thickness seemed to be improved with even higher levels of dietary SID Thr level.